2018
DOI: 10.3382/ps/pex430
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of refined functional carbohydrates from enzymatically hydrolyzed yeast on the transmission of environmental Salmonella Senftenberg among broilers and proliferation in broiler housing

Abstract: Hatching eggs collected from resident broiler breeders at 48 wk of age were used to produce male and female chicks that were assigned sex separately to 96 new litter pens and fed either a 0 or 50 g/MT RFC (refined functional carbohydrate feed additive derived from yeast) diet. There were 24 replicate pens of 12 broilers each per diet per sex. Feed intake and BW were determined at 14, 28, and 42 d of age. Litter was sampled by pen using sterile socks at 35 d and tested for Salmonella spp. using an enzyme linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…It is inferred that supplementation of SYF in the diet helps to improve the feed conversion before the breeding stage of pullets, and the decrease of BW caused by Salmonella infection in chicks was significantly eased, which is consistent with previous research reports listed here. Refined functional carbohydrate feed additive derived from yeast supplemented in the diet increased the weight gain, daily gain and feed intake (Walker et al, 2018 ). As the dosage increased, there is an uptrend.…”
Section: Discussionmentioning
confidence: 99%
“…It is inferred that supplementation of SYF in the diet helps to improve the feed conversion before the breeding stage of pullets, and the decrease of BW caused by Salmonella infection in chicks was significantly eased, which is consistent with previous research reports listed here. Refined functional carbohydrate feed additive derived from yeast supplemented in the diet increased the weight gain, daily gain and feed intake (Walker et al, 2018 ). As the dosage increased, there is an uptrend.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic hydrolysis of yeasts produces cell‐free culture supernatant that show activity against Gram‐negative bacteria. Previous studies have shown that refined functional carbohydrates can agglutinate as well as inhibit adherence of several species of Salmonella to the intestinal epithelium inhibiting them from colonizing the digestive tract (Walker et al , ). Singh et al () also showed that refined functional carbohydrates have effects on cytokine gene expression, including the genes encoding for pro‐inflammatory cytokines and T helper (T1and T2), which enhances the immune function of sexually mature hens.…”
Section: Probiotic Yeast For Poultrymentioning
confidence: 99%
“…The following samples were collected from BF1 as described by Walker et al. (2018) : feed samples from each experimental diet at the feed mill, chick paper, and eggshells in the hatchery at day of hatch, a pre-enriched sock applied to litter floor pens at 15 D, and individual ceca at 44 D. Samples were suspended in 1% buffered peptone water ( BPW ) and maintained on ice until further enrichment and incubation occurred.…”
Section: Methodsmentioning
confidence: 99%
“…After initial enrichment for all samples, Salmonella spp. identification was achieved with an enzyme-linked fluorescence assay automated instrument (VIDAS 30 Multi-parametric Immunoassay Instrument, BioMérieux, Inc., Marcy-l’Étoile, France) and confirmed by culture with Rapid Salmonella Agar (Bio-Rad #3563961; Hercules, CA) and XLT-4 agar (Oxoid Product #CM1061) as described by Walker et al. (2018) .…”
Section: Methodsmentioning
confidence: 99%